2005
DOI: 10.1302/0301-620x.87b2.15394
|View full text |Cite
|
Sign up to set email alerts
|

Stability of the Birmingham hip resurfacing arthroplasty at two years

Abstract: The Birmingham hip resurfacing metal-on-metal arthroplasty was introduced in 1997 and has shown promising short- to mid-term results. We used radiostereophotogrammetric analysis (RSA) to study the stability of 20 resurfacing arthroplasties over a follow-up period of 24 months. Radiological examinations for RSA were performed immediately after surgery and at two, six, 12 and 24 months after operation. Precision and detection of migration thresholds (non-zero movement) were calculated. All the results correspond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 13 publications
4
43
0
Order By: Relevance
“…Previous reports demonstrate the fixation of implants is excellent with low rates of implant failure [8,27,28,34,66]. Our study demonstrated patients with resurfacing were highly satisfied with their procedure and attained a high level of satisfaction across multiple domains including pain relief, function, and ability to participate in recreation.…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…Previous reports demonstrate the fixation of implants is excellent with low rates of implant failure [8,27,28,34,66]. Our study demonstrated patients with resurfacing were highly satisfied with their procedure and attained a high level of satisfaction across multiple domains including pain relief, function, and ability to participate in recreation.…”
Section: Resultssupporting
confidence: 63%
“…The modern era of hip resurfacing began in 1990, and it became clear by 1996 a metal-on-metal device with hybrid fixation could produce results comparable to THA [46]. Total hip resurfacing arthroplasty with a metal-on-metal articulation has perceived advantages: the preoperative anatomy is better replicated than with the more traditional THA [34]; proximal femoral bone stock is preserved under a physiologic loadbearing pattern [4,37]; metal-on-metal articulations have a low wear rate, thus potentially eliminating osteolysis [48]; and the large femoral heads minimize the risk of dislocation [14,15]. It is currently estimated resurfacing arthroplasty accounts for up to 9% to 11% of all THAs in countries where this technology has been readily available for the last 5 years [12,23,35,50,[62][63][64].…”
Section: Introductionmentioning
confidence: 99%
“…Roentgen stereophotogrammetric analysis (RSA) has become a well-established technique for monitoring the migration of prostheses fixed to bone. 11 RSA was developed to measure the change in relative position of one rigid body in relation to another, and these rigid bodies are usually defined by use of clusters of small metal beads. Thus, to gain access to the high accuracy offered by the RSA method so that it could be used to monitor migration of the tendon away from the bone in rotator cuff repairs, it was necessary to develop a novel method for its use.…”
mentioning
confidence: 99%
“…Considering that this number is lower than data previously reported for failed cemented components the authors summarized, that the Birmingham hip resurfacing is likely to perform well in the long term. While this study used the outer circumference of the femoral component head and tip of the stem to measure migration a more recent study equipped the implants with tantalum markers and therefore was able to evaluate rotation of the components as well [39]. This study confirmed minimal translational (less than 0.1 mm in all directions) and rotational (less than 1 degree) movements within the first 24 months after implantation.…”
Section: Use Of Rsa In the Evaluation Of Modern Implant Designsmentioning
confidence: 70%